Residue behavior and safety evaluation of pymetrozine in tea. (3rd February 2021) - Yu, Huan; Sun, Hezhi; Wang, Xinru; Liang, Yabo; Guo, Mingming; Yu, Jiawei; Yang, Mei; Zhang, Xinzhong; Luo, Fengjian; Zhou, Li
Abstract: BACKGROUND: Pymetrozine is a widely used pesticide. It is challenging to analyze and difficult to manage due to the large gap in its global maximum residue limits (MRLs) in tea. The development of a high‐efficiency detection method for the evaluation of the transfer of residual pymetrozine from tea plantations to tea cups is therefore of prime significance. RESULTS: An analytical method for the determination of pymetrozine residues in tea was established based on Cleanert PCX solid‐phase extraction. The average recoveries were 72.2–93.7%, with relative standard deviations (RSDs) of less than 12%. The limits of quantification (LOQs) were 0.005 mg·kg −1 in fresh tea leaves and dry tea, and 0.00025 mg·L −1 in tea brew. Pymetrozine degraded rapidly in tea plants with a half‐life (t1/2 ) of 1.9 days in open tea plantations, and decreased by 9.4–23.7% in the green tea‐processing procedure, which was concentration dependent. The residual pymetrozine levels in green tea collected at 6 and 21 days were below the MRLs in China and EU at a dosage of 30 g a.i. ha −1, respectively. The leaching rates of pymetrozine from dry tea to tea brew were 58.7–96.3%. Hazard quotient (HQ) values of pymetrozine were significantly <100% when tea shoots were plucked in 6 days, which indicated a negligible risk to humans. CONCLUSION: This work allows the determination of residual pymetrozine in tea and illustrates a low intake risk with the use of pymetrozine in tea plantations. It could serve as reference for further regulation consideration for maximum residue limits (MRLs). © 2020 Society of Chemical Industry